2000
DOI: 10.1016/s0014-5793(00)01908-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of super αA‐crystallin, a product of in vitro exon shuffling

Abstract: K KA-Crystallin, a small heat shock protein with chaperone-like activity, forms dynamic multimeric complexes. Recently we described the spontaneous generation of a mutant protein (super K KA-crystallin) by exon duplication arisen via exon shuffling confirming a classic hypothesis by Gilbert [Nature 271 (1978) 501]. Comparison of super K KA-crystallin, which is viable in a mouse skeletal muscle cell line, with normal K KAcrystallin shows that it has diminished thermostability, increased exposure of hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, this is not free of controversy (29,47). In the present study we see a complete loss in the chaperone-like function of mutant ␣A-crystallin at and slightly above physiological temperatures despite an increase in hydrophobicity.…”
Section: F71g Mutant Of ␣A-crystallinmentioning
confidence: 40%
See 1 more Smart Citation
“…However, this is not free of controversy (29,47). In the present study we see a complete loss in the chaperone-like function of mutant ␣A-crystallin at and slightly above physiological temperatures despite an increase in hydrophobicity.…”
Section: F71g Mutant Of ␣A-crystallinmentioning
confidence: 40%
“…They concluded that there is no correlation between surface hydrophobicity and chaperone-like activity. Experiments with super-␣A-crystallin have indicated that the disappearance of chaperone-like activity may be independent of hydrophobicity (47). Further, Reddy et al (18) have shown recently that hydrophobicity is not the sole determinant of chaperone-like activity in ␣-crystallin.…”
Section: F71g Mutant Of ␣A-crystallinmentioning
confidence: 99%
“…In other words, ANS binding studies did not show the correlation between the probe binding properties and chaperone activity as shown by bis-ANS and pyrene. Our own studies 2 and those from another laboratory (61) show that ANS binding and chaperone activity of some mutants of ␣-crystallin do not correlate. Our earlier study (18,28) on temperature-dependent chaperone activity and ANS binding or pyrene solubilization of the wild type ␣-crystallin showed good correlation.…”
Section: Figmentioning
confidence: 74%
“…As a case in point, oligomers lacking chaperone activity arise from chimeric α‐crystallins [63]. Also, insertion of a peptide [41,64] and change of a single residue [10,11,13,65] lead to enlarged oligomers with curtailed chaperone action in vitro. In other work, dissociation of oligomers was a prerequisite for chaperoning in vitro [66], and disassembly of active units from an oligomeric (storage) state of α‐crystallin was proposed, upon structural analysis of αA‐crystallin by site‐directed spin labelling, as a model for chaperone function [67].…”
Section: Discussionmentioning
confidence: 99%
“…Chaperoning is thought to depend upon formation of oligomers that reach 800 kDa in mass and possess quaternary structure modifiable by environmental parameters [8,18,20,22,39,40]. Oligomers exhibit dynamic equilibrium with constituent subunits, which can affect chaperoning but is not in itself sufficient to ensure chaperone activity [25,41,42]. A small heat shock/a-crystallin protein from Methanococcus jannaschii, termed Mj hspl6.5, has been crystallized, revealing highly ordered oligomers of 24 subunits with a hollow center [9].…”
mentioning
confidence: 99%